Fabrication of organic-inorganic bridged polysilsesquioxane (BPS) matrix containing polycarbonate diol (PCD) units for solid polymer electrolytes (SPEs). (12th December 2017) - Oh, Sinseok; Kim, Seongkwan; Lee, Yongpyo; Lim, Jung-Hyurk; Kim, Ki-Young; Kim, Kyung-Min
ABSTRACT: New type of solid polymer electrolytes (SPEs) were synthesized by polycarbonate diol (PCD)-based bridged polysilsesquioxane (BPS) monomer and lithium bis(trifluoromethane)sulfonimidate (LiTFSI) via the sol-gel process. The ion conductivity of PCD-based BPS matrix was increased from 1.41 × 10 −7 to 4.09 × 10 −5 ((Ω · cm) −1 ) according to the amount of lithium salts at room temperature. The effect of lithium salts to the ion conductivity is attributed to the homogenous dispersion of lithium salts into the SPEs matrix. The thermal stability of PCD-based BPS matrix is higher than that of PCD oligomer and PCD-based BPS monomer in thermogravimetric analysis (TGA).